Perspectives on Social Suffering in Interviews and Drawings of Palestinian Adults Crossing the Qalandia Checkpoint: A Qualitative Phenomenological Study - Nagamey, Nihal M.; Goldner, Limor; Lev-Wiesel, Rachel (Frontiers in Psychology, 2018)
The current study examined the psychological experience of Palestinians who daily cross an Israel Defense Forces (IDF) checkpoint to reach their schools or places of employment. The study employed an interpretative phenomenological analysis of semi-structured interviews and drawings to capture a depth insight regarding the psychological meaning of crossing the Qalandia checkpoint on a daily basis among twenty adult participants (ten males, ten females). Three themes emerged. The first theme described deep feelings of distress and desperation and included the categories of humiliation and dehumanization, nonexistence, rage, and pessimism and helplessness. The second theme concentrated on the participants' coping strategies of avoidance and dissociation, which usually characterize maladaptive trauma coping style, as well as exhibited aggressiveness toward their fellow community members, while the third theme described the social fragmentation of the Palestinians' solidarity. Furthermore, three pictorial phenomena emerged from the participants' drawings: squared restricted drawings, the use of multiple black tiny objects, and the use of split drawings. These phenomena supported and validated participants' verbal expressions. We suggest understanding these findings in light of the term "social suffering."